2014
DOI: 10.1007/s00431-014-2419-y
|View full text |Cite
|
Sign up to set email alerts
|

Nasal high-frequency oscillation ventilation in neonates: a survey in five European countries

Abstract: In a number of European NICUs, clinicians use nHFOV. The present survey identified differences in nHFOV equipment, indications, and settings. Controlled clinical trials are needed to investigate the efficacy and side effects of nHFOV in neonates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
72
5
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 34 publications
8
72
5
3
Order By: Relevance
“…Several modern neonatal ventilators are technically able to provide NHFOV, although their performance may be variable at extreme settings or for term neonates 8 9. A recent European survey described wide variation in the type of device used to provide NHFOV 5. A new concept has also been recently introduced, as bench experiments demonstrated the feasibility of generating NHFOV through the control of fan and valve: this allows designing a ventilator specifically dedicated only to NHFOV 10…”
Section: Basic Principles Of Nhfovmentioning
confidence: 99%
See 3 more Smart Citations
“…Several modern neonatal ventilators are technically able to provide NHFOV, although their performance may be variable at extreme settings or for term neonates 8 9. A recent European survey described wide variation in the type of device used to provide NHFOV 5. A new concept has also been recently introduced, as bench experiments demonstrated the feasibility of generating NHFOV through the control of fan and valve: this allows designing a ventilator specifically dedicated only to NHFOV 10…”
Section: Basic Principles Of Nhfovmentioning
confidence: 99%
“…Regarding the effects linked to a non-invasive interface, it is conceivable that having an oscillating interface on the skin could produce some local reactions or skin injuries, but this has never been studied, and a European survey has not described skin injuries among the side effects of NHFOV 5. Early HFOV has been claimed to be less pro-inflammatory than conventional ventilation34 and one could imagine the same effect for NHFOV as compared with conventional NIV.…”
Section: Biological Effects Of Nhfovmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent European survey reported that 17% were using noninvasive HFOV for diverse indications, mainly for CPAP failure or as primary therapy. There were significant variations in the types of equipment, interfaces and settings used for its delivery, with little information about its safety profile [33]. Similarly, noninvasive NAVA is increasingly applied in many NICUs across North America using evidence mainly based from animal data, retrospective clinical studies and case series [34].…”
Section: Noninvasive Ventilationmentioning
confidence: 99%